Improved Diagnosis of Pancreatic Adenocarcinoma using Haptoglobin and Serum Amyloid A in a Panel Screen - Firpo, Matthew A. (2009)
PURPOSE: Timely and accurate diagnosis of pancreatic adenocarcinoma (PA) is hampered by the lack of effective circulating biomarkers. No single test has emerged that improves upon the commonly used biomarker, cancer antigen 19-9 (CA 19-9) to effectively discriminate PA from benign conditions. The goals of this study were to validate two acute phase proteins, haptoglobin and serum amyloid A (SAA), as biomarkers for PA and determine if the combination of haptoglobin, SAA and CA 19-9 would improve PA diagnosis over CA 19-9 alone. METHODS: Levels of haptoglobin, SAA and CA 19-9 were measured in pre-treatment sera from 75 PA patients, 32 patients with chronic pancreatitis, 42 patients with other benign pancreatic disease or biliary stricture and 150 healthy control subjects by ELISA or colorimetric binding assay. Relative levels of haptoglobin or SAA were compared between groups using ANOVA. The diagnostic accuracy of serum haptoglobin and SAA levels were investigated using receiver operating characteristics analysis. Using classification tree analysis, an algorithm was developed that used haptoglobin, SAA and CA 19-9 in a panel diagnostic screen. RESULTS: Both haptoglobin and SAA were significantly elevated in sera from PA patients compared to healthy control subjects (P < 0.0001) and patients with chronic pancreatitis (P = 0.01). Haptoglobin was significantly elevated in sera from PA patients relative to patients with other benign diseases (P = 0.0015), whereas SAA fell short of significance in the same comparison (P = 0.0508). Receiver operating characteristic analysis indicated that haptoglobin (AUC = 0.792) was a better diagnostic marker than SAA (AUC = 0.691) over multiple threshold cutoffs. Using specific cutoffs that minimized overall misclassification, haptoglobin yielded a sensitivity of 82.7 % and a specificity of 71.1% and SAA yielded a sensitivity of 34.7% and 90.2% specificity when discriminating PA cases from all non-PA controls. In the same sample set, CA 19-9 yielded a sensitivity of 77.3% and a specificity of 91.1%. Combining data from haptoglobin, SAA and CA 19-9 in a panel diagnostic screen improved overall accuracy over CA 19-9 alone yielding a sensitivity of 81.3% and a specificity of 95.5%. CONCLUSIONS: These data demonstrate that haptoglobin and SAA are useful in discriminating PA from benign conditions as well as healthy controls when used in a panel diagnostic screen. This study supports the use of combined biomarkers for improved accuracy in the diagnosis of PA.